Terahertz strong-field physics in light-emitting diodes for terahertz detection and imaging - Chen Ouyang (Nature Portfolio, 2021)
Interest in the exploration of non-perturbative nonlinear optical phenomena driven by intense terahertz fields has seen a leap forwards with the recent development in femtosecond laser-based table-top sources for strong THz radiation. The authors present intense THz-field-induced effects in ubiquitously available LEDs illuminated by strong THz pulses, paving the way to their use in detecting and imaging intense THz radiation.